Key recommendations for antimicrobial resistance surveillance: takeaways from the CAPTURA project - Aboushady, Ahmed; Sujan, Mohammad Julhas; Pham, Kien; Clark, Adam; Marks, Florian; Holm, Marianne; Joh, Hea Sun; Poudyal, Nimesh; Stelling, John (Clinical infectious diseases, 2023)
Antimicrobial resistance (AMR) is a growing global public health challenge associated with 4.95 million deaths in 2019 and an estimated 10 million deaths per year by 2050 in the absence of coordinated action. A robust AMR surveillance system is therefore required to avert such a scenario. Based on an analysis of country-level AMR data in 8 Capturing Data on Antimicrobial Resistance Patterns and Trends in Use in Regions of Asia (CAPTURA) countries, we present a list of key recommendations to strengthen AMR surveillance. We propose 10 primary considerations under 3 broad categories, including recommendations on (1) laboratory and testing practices, (2) data management and analysis, and (3) data use.
Online veröffentlicht: 20. Dezember 2023
Gesehen am 06.05.2024